Psychological Factors Influencing Elementary Students’ Science Learning Difficulties: An Explanatory Study - Nur Rohmatillah; Iyoh Maspiroh; Euis Nur Istiqomah; Aep Saepudin (Journal of General Education and Humanities, 2026)
This study examines the psychological determinants of science learning difficulties among elementary school students by integrating multiple dimensions within a single analytical framework. The research is motivated by the persistent issue of low science achievement, which is often addressed in a fragmented manner. This study addresses the limited integrative analysis of multiple psychological dimensions in explaining science learning difficulties at the elementary level. Accordingly, the objective is to analyze both the simultaneous and partial effects of cognitive, affective, psychomotor, social, and emotional factors on students’ science learning outcomes. An explanatory survey design was applied involving 115 students from two elementary schools in Kuningan, West Java, Indonesia. Data were collected using validated questionnaires and analyzed through normality testing and multiple linear regression. The results indicate that all psychological dimensions collectively have a significant effect on science learning outcomes. However, partially, affective, psychomotor, and emotional factors demonstrate significant positive influences, whereas cognitive and social factors do not show significant individual effects. These findings highlight the dominant role of non-cognitive psychological aspects in shaping students’ science achievement. This study contributes by offering a holistic perspective on psychological influences in science learning, emphasizing the need for instructional strategies that strengthen motivation, emotional regulation, and active engagement to reduce learning difficulties and improve academic performance.